Measuring Methane in the Arctic Ocean - From legal framework to time series analysis via technology innovation - Dølven, Knut Ola (UiT Norges arktiske universitet, 2022)
Understanding how the earth system interacts with ongoing climate change is important to find a realistic route towards a sustainable future. The impact of Arctic seabed methane seepage on contemporary and future climate is still poorly constrained, described, and quantified. An important limiting factor in our understanding of seabed seepage in the Arctic is a lack of in situ measurements; however, remoteness and harsh environmental conditions make data acquisition difficult. The aim of this thesis is to improve understanding of and ability to measure methane in the Arctic Ocean via inter-disciplinary work, method development and time-series analysis. To fill crucial data gaps and increase the general data coverage in the region demands implementation of innovative technology and increased research activity. Legal scholars have identified emerging legal gaps associated with this increased activity and regulation of marine scientific research. However, our inter-disciplinary assessment indicates that an evolutionary interpretation of the legal framework is currently adequate to regulate and facilitate current conduct of marine scientific research in the Arctic Ocean. We obtained a unique data set from two intense seep sites (at 91 and 246 meter depth) offshore West Spitsbergen by deploying two autonomous ocean observatories which recorded respectively 10 and 3 month time-series of bottom water physical and chemical parameters between July 2015 and May 2016. High short term variability (<∼1000 nmol L −1 on hourly time-scales) were observed which were partly explained by changing ocean currents and location of nearby seeps. A seasonal variation with lower (∼halved) concentrations and variability in winter season was coupled with increased water column mixing. No clear effect of tidal hydrostatic pressure changes were observed, but a negative correlation between methane and temperature at the deepest seep site aligns well with hypothesized seasonal blocking of lateral sedimentary methane pathways. We highlighted ...